2014
DOI: 10.1159/000366374
|View full text |Cite
|
Sign up to set email alerts
|

Serum MiRNA Biomarkers serve as a Fingerprint for Proliferative Diabetic Retinopathy

Abstract: Background: Diabetic retinopathy (DR) is a retinopathy resulting from diabetes mellitus (DM) which was classified into non-proliferative DR (NPDR) and proliferative DR (PDR). Without an early screening and effective diagnosis, patients with PDR will develop serious complications. Therefore, we sought to identify special serum microRNAs (miRNAs) that can serve as a novel non-invasive screening signature of PDR and test its specificity and sensitivity in the early diagnosis of PDR. Methods: In total, we obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 25 publications
1
77
0
Order By: Relevance
“…Various recent reports have demonstrated alterations in miRNA expression in diabetic eyes. Subjects with proliferative and nonproliferative DR have different serum levels of miR-21, miR-181c, and miR-1179 [96]. Downregulation of miR-200b was observed in the retina in diabetes.…”
Section: The Role Of Epigenetics In the Pathogenesis Of Diabetic Retimentioning
confidence: 98%
“…Various recent reports have demonstrated alterations in miRNA expression in diabetic eyes. Subjects with proliferative and nonproliferative DR have different serum levels of miR-21, miR-181c, and miR-1179 [96]. Downregulation of miR-200b was observed in the retina in diabetes.…”
Section: The Role Of Epigenetics In the Pathogenesis Of Diabetic Retimentioning
confidence: 98%
“…Clinical tests, biochemical markers, and molecular factors, with the latter including genetic and epigenetic markers [4]. 2.…”
Section: Types Of Biomarkersmentioning
confidence: 99%
“…Recently, three miRNAs in serum of patients with diabetic retinopathy have been reported as potential biomarkers of the disease [4,302,306]. Our team is currently taking a discovery rather than a candidate approach to microRNAs for latestage diabetic retinopathy, and recently published a paper highlighting the impact of the instrumentation used for detection of these molecular biomarkers [85].…”
Section: Epigeneticsmentioning
confidence: 99%
“…Thus, new biomarkers would be useful to improve the detection of these complications. Interestingly, a study revealed three serum miRNAs (miR-21, -181c, -1179) that are deregulated in patients with proliferative diabetic retinopathy vs those with non-proliferative retinopathy suggesting that circulating miRs could be non-invasive biomarkers for the detection and/or the follow-up of retinopathy [66]. Furthermore, in a small cohort, a higher level of several miRNAs related to angiogenesis (miR-15a, -320a, -320b, -93, -29a) was found in vitreous humour of patients with proliferative diabetic retinopathy compared with patients with macular hole, with some of these miRNAs also deregulated in the serum [67].…”
Section: Circulating Mirnas As Biomarkers To Assess Diabetic Complicamentioning
confidence: 99%